Substrate preparation behaviors for the cultivation of the symbiotic fungus in leaf-cutting ants of the genus atta (Hymenoptera: Formicidae) - Diniz, E. A. [UNESP]; Bueno, O. C. [UNESP] (My University, 2009)
Our findings revealed two distinct patterns of substrate preparation: the pattern of leaf-cutting ants foraging on dicotyledons is marked by highly fragmented substrate' resulting in a more advanced initial decomposition. The pattern of leaf-cutting ants harvesting grasses is characterized by large pieces of substrate, resulting in little initial decomposition. Ants foraging on both types of plants are apparently intermediary between the two patterns, although more similar to the patterns of those foraging on dicotyledons. Also, the behavior of scraping the substrate was described for the first time, it is very important for the removal of the epicuticular wax layer of the leaves helping the growth of the symbiotic fungus.
Keywords: Ants; Atta; Preparation behavior; Symbiotic fungi